2005
DOI: 10.1159/000087660
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Exocrine Pancreatic Function in Type-1 Diabetes mellitus

Abstract: In a previous study, mild to moderate exocrine pancreatic insufficiency, as measured by the secretin-pancreozymin test, was found in 23 (43%) of 53 patients with type-1 diabetes mellitus. Of these 53 patients, 20 (7 of whom initially had an abnormal secretin-pancreozymin test) were available for a follow-up examination 11 years later. Of the 7 patients with abnormal exocrine pancreatic function at the first test, 5 remained abnormal and 2 became normal, whereas of the 13 patients with initially normal pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…In a German study of 20 subjects with type 1 DM, a follow-up secretin-pancreazymin test 11 years after a previously abnormal test found no significant correlation between the duration of DM and the test results for both time points of investigation. 36 In fact, only mild abnormalities in pancreatic function were observed after a mean of 22 (±10.9) years of disease. There have been conflicting results regarding FE1 levels and duration of DM; a few studies have reported that increase in the duration of DM is associated with decreased FE1 level, 50,52 but others did not find any correlation with duration of DM.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a German study of 20 subjects with type 1 DM, a follow-up secretin-pancreazymin test 11 years after a previously abnormal test found no significant correlation between the duration of DM and the test results for both time points of investigation. 36 In fact, only mild abnormalities in pancreatic function were observed after a mean of 22 (±10.9) years of disease. There have been conflicting results regarding FE1 levels and duration of DM; a few studies have reported that increase in the duration of DM is associated with decreased FE1 level, 50,52 but others did not find any correlation with duration of DM.…”
Section: Resultsmentioning
confidence: 94%
“…Multiple studies in DM have reported high prevalence of abnormal exocrine pancreatic function both on direct 16,3646 (Supplementary Table 3, http://links.lww.com/MPA/A487) and indirect pancreatic function test (FE1) (Table 3). The most common abnormalities observed by direct pancreatic function tests were decreased amylase and bicarbonate output and decreased maximum bicarbonate concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In another previous study it was demonstrated that in 74% of patients classified as type 1 diabetes mellitus steatorrhea was present and steatorrhea correlated inversely with FEC concentrations [27]. While one follow-up study in only 20 patients claimed that a progression of PEI is rare in diabetes mellitus [28], it must be concluded from the information presently available that in patients with diabetes mellitus PEI is not only very frequent in terms of pathological function tests but also in terms of fat maldigestion. This finding might explain abdominal symptoms in patients with diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear whether chymotrypsinogen plays a developmental role in the pancreas; its expression may serve simply as a marker for the developing acinar cell. In T1DM patients, mild pancreatic exocrine deficiency not requiring pancreatic enzyme replacement is noted in up to 80% of patients [25]; however, a decade later the mild exocrine insufficiency resolved, suggesting that exocrine deficiency represents an early defect following T1DM onset [26]. Chymotrypsinogen is also an autoantigen in patients with T1DM [27].…”
Section: Exploration Of Novel T1dm Genes and Pathways To Dysfunction mentioning
confidence: 99%